Implementasi Government Public Relations BNNK Jakarta Selatan pada Pencegahan Penyalahgunaan Narkoba di Kalangan Remaja - Nicky Maulana; Tria Patrianti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The high rate of drug abuse in Indonesia, particularly among adolescents, highlights the urgency of government intervention. The Indonesia Drug Report reported a prevalence of 1.73%, with 3.3 million people affected, predominantly adolescents. This research aims to delve deeper into the implementation of the Government Public Relations (GPR) function of the South Jakarta City National Narcotics Agency (BNN) in preventing drug abuse among adolescents. The research uses a qualitative approach with a case study method, employing data collection techniques such as observation, in-depth interviews, and documentation. The research results show that the implementation of the GPR function in citizen-government interactions is carried out through public communication activities by conveying information, policies, and programs and educating the public through FGD activities, advocacy, policy socialization, outreach, training, and the Bersinar campaign. Regulator communication is conducted through intensive communication between institutions such as local governments, law enforcement agencies, educational institutions, and several related stakeholders in supporting and aligning the goals of prevention policies/programs. As an extension of policy, the South Jakarta City BNN disseminates information policies and programs and educates the public by selecting messages that not only serve to convey information but also aim to build public perception, attitudes, and participation in prevention policies and programs through various communication channels, both conventional and digital, as well as mass media, based on the principles of good governance.